281 Protein C and Protein S in the Diagnosis, Management and Prognosis of Premature Infant with Necrotizing Enterocolitis. (October 2012) - Wang, LS; Cheng, GQ; Cao, Y; Shao, XM; Zhou, WH
Abstract : Objective: In this prospective, observational study, we determined whether serum protein C and protein S (PC/PS) activity correlated with necrotizing enterocolitis (NEC) stages II and III in premature infant. We hypothesized that PC/PS measurement if used as an adjunct to abdominal radiographs would improve the identification and predication of infants with NEC. Methods: Serum PC/PS activity was measured according to protocol at early stage and recover stage of NEC. When clinical signs persisted and the initial abdominal radiographs were abnormal, follow-up radiographs were obtained. Results. Of 45 infants who were evaluated for gastrointestinal signs, only 2 had ileus or benign pneumatosis intestinalis with persistently normal PC/PS; gastrointestinal manifestations resolved within 48 hours, antibiotics were discontinued in < 48 hours, and feedings were restarted early without complications. 35 infants had NEC stages II and III; all had decreased PC/PS activity regardless of their blood culture results. PC/PS activity negatively correlative with severity of NEC and positively correlative with the recover form NEC. Conclusions: In infants with suspected NEC, normal PC/PS values would favor aborted antibiotic therapy and early resumption of feedings. PC/PS becomes significantly lower in both stage II and stage III NEC. In infants with NEC, persistently decreased PC/PS after initiation of appropriate medical management suggests associated complications, which may require surgical intervention.